GAYA HIDUP DAN KEBIASAAN MAKAN MAHASISWA - Saufika, Anita; Retnaningsih, Retnaningsih; Alfiasari, Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2012)
This study aimed to analyze the influence of internal (student’s characteristics) and external factors (family’s characteristics, reference group, foods caring) on the college student’s lifestyle and to analyze the influence of internal factors, external factors, and lifestyle on food habits. This study involved 120 college students that selected by cluster random sampling. The data analysis used descriptive, cluster, and logistic regression. The result showed that the most students had an entertainment and health-oriented lifestyle. The lifestyle was influenced by student’s age, family size, and television reference group. Male students had more opportunity to eat three times a day routinely beside was influenced by increasing of father’s age and family and friends scores as reference groups. Increasing scores of friends as reference group influenced breakfast habits, meanwhile increasing scores of family as reference group influenced snack and dinner habits. Male students and housewife mother more influenced increasing of dinner habits. Moreover, female students more influenced increasing of snack habits.